REKONSTRUKSI KURIKULUM PENDIDIKAN ISLAM BERBASIS ARTIFICIAL INTELLIGENCE DALAM PENGUATAN AKHLAK SISWA MADRASAH: STUDI KEPUSTAKAAN - Afif Syaiful Mustofa; Zamroni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to reconstruct an Artificial Intelligence (AI)-based Islamic education curriculum to strengthen the moral character (akhlaq) of madrasah students. The study is motivated by the gap between the rapid development of educational technology and the current implementation of Islamic education curricula, which remain predominantly cognitive-oriented and lack systematic integration of moral values. This research employs a qualitative approach with a library research design by analyzing relevant scholarly literature on AI, Islamic education curriculum, and moral education. The findings indicate that the integration of AI into the Islamic education curriculum can be achieved through reconstruction of curriculum components, including objectives, content, teaching methods, and assessment, with a primary focus on moral development. AI functions as a wasilah (instrument) to support personalized learning, monitor students’ character development, and facilitate contextual value internalization through technologies such as adaptive learning and learning analytics. However, the implementation of AI must remain guided by Islamic values, with teachers maintaining a central role as moral and spiritual mentors. This study contributes theoretically to the development of an integrative technology-based Islamic curriculum model and offers practical implications for designing adaptive madrasah curricula that prioritize students’ moral development in the digital era.